Sexuality and the world's religions - Machacek, David W.; Wilcox, Melissa M. (ABC-Clio, 2003)
Exploring one of the most controversial topics in contemporary theology, this scholarly volume reveals what the world's great faiths-East and West-preach about sexuality, with a special emphasis on American religion.http://www.abc-clio.com/products/overview.aspx?productid=108834&viewid=0